Exploring the levels of knowledge, attitudes and environment-friendly practices among young civil servants in Malaysia - Awang Besar, Tan; Hassan, Md. Salleh; Bolong, Jusang; Abdullah, Ramdzani (Universiti Putra Malaysia Press, 2013)
Today's younger generations will determine the future and progress of the country. It is therefore important to create and nurture mature behaviour in younger generations towards the environment. Such behaviour is vital to ensure that the environment is continually protected and conserved. Exploring the levels of knowledge, attitudes and environment-friendly practice in young civil servants is an initial step in designing an environmental programme that will empower youth in leading and promoting recycling as one environment-friendly response to a threatened environment. To achieve this purpose, this study utilised the Knowledge, Attitudes and Practice (KAP) Model to examine the levels of knowledge, attitudes and workplace recycling practice among young civil servants. The study involved 244 young civil servants randomly selected from administration or management divisions in 25 government agencies aged between 20 and 40 years. The findings reveal that the level of knowledge and attitudes among the young civil servants on recycling was remarkable. However, the level of recycling practice at the workplace is moderate. Both recycling knowledge and attitudes are predictors of workplace recycling practice among young civil servants. Thus, any intervention programme involving youth to improve recycling should consider these results as a basis in designing a programme that can equip youth with some abilities and skills in proper recycling methods. With this knowledge, they can inspire their colleagues to actively participate in office recycling. practices. In addition, these well-trained young civil servants can also be appointed to become change agents in promoting, educating and enhancing recycling practices in their neighbourhood. Civil servants not only serve the people, but can also lead in voluntary community environment-friendly activities. Indeed, they should be encouraged to do so.